Variable course of progression of oral cavity and oropharyngeal carcinoma in young adults - Pabiszczak, Maciej Szczepan; Waśniewska, Elżbieta; Mielcarek-Kuchta, Daniela; Miętkiewska-Leszniewska, Dorota; Wierzbicka, Małgorzata; Szyfter, Witold (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The main aim of this article is the epidemiological analysis of patients treated due to oral and oropharyngeal cancer, with a special interest in the group under the age of 40, evaluation of the differences in the clinical course of the disease as well as assessment of the treatment results, regarding the age of the affected individuals. Material and methods : 523 individuals affected by oral and oropharyngeal cancer who were treated in the Otolaryngology and Laryngeal Oncology Department between 2000 and 2008. Precise analysis was performed on 360 out of 523 affected individuals, in whom full clinical status was determined; 13 patients were young adults. The retrospective analysis was created based on case histories, surgical protocols and emergency records. Results : In young adults there is a markedly increased risk of organ involvement according to the Mann-Whitney U-test analysis (p = 0.044907). The probability of recurrence in the group of young adults is also much higher. Analysis of Kaplan-Meier test results indicated that the chance for the lack of recurrence within a 6-month period was 85.7%; however, the risk of recurrence increased, and after 12 months was equal to the arithmetic data (50%). Conclusions : Among young adults there is an increased risk of local recurrence following 12 months after surgical intervention. According to our observations, despite rapid progression and early recurrence in young adults (4/7) the prognosis for both groups is not statistically different.